THE ASSOCIATION BETWEEN DEMOGRAPHIC CHARACTERISTICS AND ONLINE LEARNING SATISFACTION - Sigit Ambar Widyawati; Cahya Tri Purnami; Hanifa M. Denny; Dian Ratna Sawitri; Sudiro Sudiro (International Journal Labs, 2022)
Online learning platforms have been popular since the spread of COVID-19 worldwide. Most universities in Indonesia switched from face-to-face teaching and academic activities to online engagements during the peak of COVID-19 cases. Previous studies found that dissatisfaction was a concern during online learning. This research investigated the association between demographic characteristics and online learning satisfaction. This study employed a cross-sectional and quantitative approach. The researchers distributed the google form questionnaires via several lecturer's social media groups of universities in Central Java Province and gathered a total of 1386 respondents. The descriptive cross-tabulation and chi-square tests resulted in respondents' profiles of college students who were <24 years old (88.5%), not married (89.8%), had no part-time job besides studying (86.5%), and attended bachelor's degrees in various fields (70.5%). Fifty percent of the respondents expressed that they have some limitations in engaging with online learning, and 30 percent were satisfied with their online learning. Age (p- value=0.0001), marital status (p-value=0.0001) and engagement in part-time job ( p-value=0.0001) were significantly associated with the online learning satisfaction. In conclusion, this study confirms other studies that online learning platforms are associated with constraints and satisfaction issues.